2020
DOI: 10.1021/acs.jpcc.0c01666
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Sensitivity Factors Based on Highly Active CO2 Methanation Catalysts Prepared via the Polygonal Barrel-Sputtering Method

Abstract: This study elucidates the factors reducing the CO 2 methanation reaction temperature of TiO 2 -supported Ru catalysts prepared via the polygonal barrel-sputtering method (Ru/TiO 2 (BS)) to investigate the structure-sensitivity mechanism. The smaller nanoparticles deposited in Ru/ TiO 2 (BS) (<4 nm) were amorphous RuO 2 because of air exposure after the preparation, and their surfaces were changed to island-shaped structures consisting of amorphous RuO 2 and amorphous Ru metal by H 2 exposure. In this case, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…No obvious desorption peak was observed at temperatures above 400 °C. For Ru/TiO 2 , the two peaks centered at 75 °C and 160–200 °C are ascribed to the hydrogen desorption from different metallic Ru sites, while the peak at 275 °C is generally attributed to the desorption of spilt-over hydrogen species. , The amounts of hydrogen desorbing from the catalysts are shown in Table S4. Over Ru/TiO 2 and Ru/Cl/TiO 2 catalysts, the amounts of hydrogen desorbing at around 75 °C are almost the same, which indicates that the ability for hydrogen adsorption and activation of these catalysts is presumably comparable between the Cl-modified and unmodified catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…No obvious desorption peak was observed at temperatures above 400 °C. For Ru/TiO 2 , the two peaks centered at 75 °C and 160–200 °C are ascribed to the hydrogen desorption from different metallic Ru sites, while the peak at 275 °C is generally attributed to the desorption of spilt-over hydrogen species. , The amounts of hydrogen desorbing from the catalysts are shown in Table S4. Over Ru/TiO 2 and Ru/Cl/TiO 2 catalysts, the amounts of hydrogen desorbing at around 75 °C are almost the same, which indicates that the ability for hydrogen adsorption and activation of these catalysts is presumably comparable between the Cl-modified and unmodified catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional processes operate at temperatures higher than 350 °C, with important drawbacks such as catalyst stability, increased CO production by Reversed Water Gas Shift reaction (RWGS), and high energy consumption. The interest in operating at low temperatures (i.e., below 200 °C) to overcome these limitations has been analysed by several authors (1)(2)(3)(4)(5)(6)(7)(8) and supported by an in deep techno-economic simulation analysis performed by Yang et al, (1). However, working at low temperatures requires to overcome the kinetic limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the catalytic performance of methanation catalysts is closely related to the nature of the support, whose specific surface area, surface basicity, interactions with active metal, oxygen vacancy, and crystal phase/plane would significantly regulate the activity and/or selectivity. Titanium dioxide (TiO 2 ) has been widely used as an efficient support in CO 2 methanation. The methanation performance over TiO 2 -supported catalysts was reported to depend sensitively upon the surface structure of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kolb’s group reported that the TiO 2 (001) plane would facilitate the dispersion of Ru species and promote the activation of CO 2 , endowing the Ru/TiO 2 catalyst with enhanced activity and improved stability . Inoue et al ascribed the optimal methanation activity of Ru/TiO 2 to the structural sensitivity originating from the polygonal barrel-sputtering method . Li and co-workers found that CH 4 selectivity over Ru/TiO 2 catalysts was boosted by increasing the proportion of rutile TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation